Make A Match untuk Meningkatkan Hasil Belajar Pendidikan Agama Kristen - Raditya Wardhani (Jurnal Didaktika Pendidikan Dasar, 2021)
This study aims to describe Make A Match based on dart game with paper chain to improve learning outcomes of Christian Religious Education's students at class VIII D in SMPN 13 Surakarta of Even Semester Academic Year 2019/2020. The subjects of this study were students of class VIII D SMPN 13 Surakarta in the 2019/2020, totaling 6 childresn. This research is a Classroom Action Research to improve the quality lerning in the classroom. Data was collected through observation, tests, and documentation. Data analysis was carried out to make conclusions and descriptions of the data based on the conditions as they were. The result showed that make a match based on dart game with paper chain can improve learning outcomes in the first cycle of action. The percentage of results in action cycle I and II wihich values above the KKM before action is 4 children or 66,67% becomes 3 children or 50%in action cycle I and 1 children or 16,67% in action cycle II.